Closing the Window of Vulnerability: Nuclear Proliferation and Conventional Retaliation. (1st January 2019) - Ludvik, Jan
Abstract: Living with a nuclear-armed enemy is unattractive, but, strangely, states seldom use their military power to prevent the enemy's entry into the nuclear club. It is puzzling why preventive strikes against nuclear programs have been quite rare. I address this puzzle by considering the role of conventional retaliation, a subfield of deterrence that so far has received scant attention in the literature. I theorize the concept of conventional retaliation and test its explanatory power. First, I explore all historical cases where states struck another state's nuclear installations and find none occurring when the proliferator threatened conventional retaliation. Second, I explore two cases where a strike was most likely, but the would-be attacker balked and find smoking-gun evidence that the threat of conventional retaliation restrained the would-be attacker. This evidence supports my claim that the threat of conventional retaliation is sufficient to deter a preventive strike against emerging nuclear states.